2008
DOI: 10.1128/aac.00283-08
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acid Fluorescent In Situ Hybridization for Hospital-Acquired Enterococcal Bacteremia: Delivering Earlier Effective Antimicrobial Therapy

Abstract: Hospital-acquired vancomycin-resistant enterococcal bacteremia has been associated with increased hospital costs, length of stay, and mortality. The peptide nucleic acid fluorescent in situ hybridization (PNA FISH) test for Enterococcus faecalis and other enterococci (EFOE) is a multicolor probe that differentiates E. faecalis from other enterococcal species within 3 h directly from blood cultures demonstrating gram-positive cocci in pairs and chains (GPCPC). A quasiexperimental study was performed over two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 39 publications
5
118
0
Order By: Relevance
“…85 CDSSs can take many forms, including comprehensive computerized disease management systems that can integrate clinical data, medication orders, and laboratory and microbiology results to suggest anti-infective therapy and alert clinicians about potential suboptimal management of infections. [86][87][88][89] Several studies of rapid blood culture diagnostics report favorable outcomes when rapid test results are reported together with CDSSs that provide actionable guidance for clinicians through antimicrobial stewardship team oversight [90][91][92][93][94][95][96][97] or even templated comments contained within the result report. 84 Increasingly, electronic health records platforms such as Epic and Cerner are incorporating CDSSs to enhance antimicrobial stewardship.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…85 CDSSs can take many forms, including comprehensive computerized disease management systems that can integrate clinical data, medication orders, and laboratory and microbiology results to suggest anti-infective therapy and alert clinicians about potential suboptimal management of infections. [86][87][88][89] Several studies of rapid blood culture diagnostics report favorable outcomes when rapid test results are reported together with CDSSs that provide actionable guidance for clinicians through antimicrobial stewardship team oversight [90][91][92][93][94][95][96][97] or even templated comments contained within the result report. 84 Increasingly, electronic health records platforms such as Epic and Cerner are incorporating CDSSs to enhance antimicrobial stewardship.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…Overall, we found that patients in the post-BC-GP group obtained the fi rst dose of optimal antibiotics 19 hours faster; additionally, more of these patients received optimal antibiotics. Other studies have shown that rapid identifi cation of organisms in blood cultures has many benefi ts, such as faster time to optimal antimicrobials (5-7), decreased length of hospital stay (7), and decreased overall hospital costs (5,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The results were ascribed to better effective therapy by ruling out the potential of contamination. Similarly, in patients with VRE bacteremia, Forrest et al showed that implementation of E. faecalis/OE PNA FISH™ (AdvanDx) reduced the time for switching from initial inadequate therapy (as reported by Ibrahim [3]) to targeted effective therapy from 3.1 to 1.3 days, thereby reducing the 30-day mortality rate from 45 to 26% [14]. Other studies have demonstrated that the use of a PNA FISH test for distinguishing C. albicans from non-C. albicans candidemia reduced antifungal costs by US$1700/patient without compromising patient safety by encouraging earlier de-escalation from broad-spectrum echinocandin to generic fluconazole for the treatment of C. albicans [15].…”
Section: Diagnostic Information That Drives Better Use Of Existing Anmentioning
confidence: 99%